ANALISIS RISIKO LIKUIDITAS PADA BANK UMUM SYARIAH DI INDONESIA - Yulfiswandi, Yulfiswandi; Halim, Rynando Sadrakh (Universitas Nusa Cendana, 2024)
Sharia Commercial Banks in Indonesia are experiencing rapid growth, as can be seen from the significant increase in sharia banking assets. As a result, Sharia Commercial Banks need to ensure bank liquidity is well maintained. This research evaluates the influence of liquidity and macroeconomic factors on the profitability of Sharia Commercial Banks. This research uses quarterly financial report data from 13 Sharia Commercial Banks during the 2018-2022 period. Sampling technique that used in this research was purposive sampling. The analysis method used is panel data regression. The research results show that the LATA and INF variables have a significant positive influence on ROA, while the CUR variable has a significant negative influence on ROA. Meanwhile, the LATD, FDR and GDP variables do not have a significant influence on ROA. Keywords: Sharia Commercial Banks; Liquidity Risk; Macroeconomics; Bank Profitability